Impact of Variation Orders on Time and Cost in Mega Hydropower Projects of Pakistan - Hanif, Hashim; Khurshid, Muhammad Bilal; Lindhard, Søren Munch; Aslam, Zuhaib (Penerbit Universiti Sains Malaysia, 2016)
The occurrence of variation orders (VOs) in the construction industry is a regular trend all over the world. Hydropower projects are no exception, and it is difficult to find a hydropower project in Pakistan that does not experience VOs. The current research investigates the causes and impacts of VOs in mega hydropower projects using case studies of three mega hydropower projects in Pakistan. The results illustrate that errors and omissions in design, changes in scope and changes in design were among the three top contributing factors to VOs in hydropower projects that resulted in time and cost overruns. Because of VOs, the time overrun is 20%, and the cost overrun is 31% with respect to the planned time and cost of the project. Based on this research, the study recommends measures to curb the causes and impacts of VOs to optimise the construction process of mega hydropower projects.